2022
DOI: 10.1111/jop.13343
|View full text |Cite
|
Sign up to set email alerts
|

Factors important in the correct evaluation of oral high‐risk lesions during the telehealth era

Abstract: Background: Considering that early detection of squamous cell carcinoma (SCC) improves prognosis and clinical examination is the primary detection method, we identified factors related to the clinical evaluation of oral mucosal lesions. Due to the growing role of telehealth, our study was based on clinical image evaluation.Subjects and Methods: Oral medicine specialists and dental students evaluated six images of benign, potentially malignant, or SCC lesions (18 images in total). We analyzed the role of person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In contrast, Czerninski et al, reported a different perspective, wherein surface appearance was considered as the most important parameter, while size was regarded as least important. They also noted that irregularity of the lesion emerged as the most crucial factor in diagnosis [ 28 ]. This discrepancy may be attributed to differences in case selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Czerninski et al, reported a different perspective, wherein surface appearance was considered as the most important parameter, while size was regarded as least important. They also noted that irregularity of the lesion emerged as the most crucial factor in diagnosis [ 28 ]. This discrepancy may be attributed to differences in case selection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we utilized clinical images of nicotine stomatitis, geographic tongue, aphthous ulcer, hairy tongue, oral candidiasis, and lichen planus. In contrast, the previous study focused on clinical images of high-risk lesions such as oral squamous cell carcinoma [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be justified because, besides color, OL classification contemplates other clinical aspects, such as surface texture and lesions boundaries. Another study revealed that besides color, other features in the clinical evaluation were also important, meaning size, margin, surface appearance, and irregularity 11 . Another fact is that during the questionary, it became notable that the experts based the classification mostly on their own experience and did not really hold on to the 3D plot interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Czerninski et al 1 used clinical pictures to distinguish benign lesions from potentially malignant and malignant pathologies. In context to Asia and Southeast Asia region, large population of patients suffering from oral submucous fibrosis (OSMF) might exhibit oral squamous cell carcinoma (OSMF-OSCC) concomitantly.…”
mentioning
confidence: 99%